Attention: the claustrum. Issue 8 (August 2015) - Goll, Yael; Atlan, Gal; Citri, Ami
Highlights: The claustrum is intriguing and worthy of attention. Robust reciprocal communication flows between cortical modalities and the claustrum. We propose a role for the claustrum in segregating attention. Abstract : The claustrum is a mysterious thin sheet of neurons lying between the insular cortex and the striatum. It is reciprocally connected with almost all cortical areas, including motor, somatosensory, visual, auditory, limbic, associative, and prefrontal cortices. In addition, it receives neuromodulatory input from subcortical structures. A decade ago, Sir Francis Crick and Christof Koch published an influential review proposing the claustrum as the 'seat of consciousness', spurring a revival of interest in the claustrum. We review the literature on the claustrum, emphasizing recent discoveries, and develop a detailed hypothesis describing a role for the claustrum in the segregation of attention.